Studi Fenomenologi: Spirit Kearifan Lokal Luwu dalam Penetapan Harga Jual Durian - Riyanti; Rifqa Ayu Dasila; Intan; Shopiah (Owner : Riset dan Jurnal Akuntansi, 2024)
This research attempts to explore and uncover the meaning of pricing determination by durian sellers. This study employs a qualitative method with a phenomenological approach as the methodology, involving data collection through in-depth interviews, passive participation, and documentation. The research indicates that durian sellers in the Latuppa Village tend to disregard the Cost of Goods Sold (COGS) calculation. The local wisdom of Sipakatuo and the values of kinship embedded in COGS serve as the basis for determining the selling price of durian. The affordable selling price of durian for the informants is conceptualized as a "sense" of mutual support and love for one another.